IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR LAJU REAKSI SISWA - Aisyatur Radhwa Marpaung; Ani Sutiani (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
One of the subject matter of Chemistry High School which has quite extensive studies and full of concepts is Reaction Rate. The subject matter will be more precisely taught through Problem Based Learning (PBL) with scientific approach that designed with surrounding environment. This study aims to determine difference between increasing learning outcomes learned through PBL with scientific approach and increasing learning outcomes learned through Direct Instruction (DI) with scientific approach on Reaction Rate. The population was all students of XI MIA MAN. The sampling technique in this study was purposive sampling. The results showed an increase in student learning outcomes in experimental class by 84% and in control class by 79%. Based on test of the real difference with the statistical technique t at the level of significance α = 0.05 on the results of this study it can be concluded that increase in student learning outcomes through the PBL with scientific approach is higher than increase in learning outcomes taught through the DI with scientific approach to Reaction rate.